2011
DOI: 10.1186/1477-7525-9-93
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients after retropubic prostatectomy - Pre- and postoperative scores of the EORTC QLQ-C30 and QLQ-PR25

Abstract: BackgroundPatients with newly diagnosed early stage prostate cancer (PCa) face a difficult choice of different treatment options with curative intention. They must consider both goals of optimising quantity and quality of life. The quality of life (QoL) is a psychometric outcome which is measured using validated questionnaires. Only few data are published concerning pre - and postoperative QoL.MethodsThis study investigated pre perative QoL of 185 patients who consecutively underwent open radical retropubic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
3
5
1
1
Order By: Relevance
“…In addition, physical, emotional, and cognitive functioning and global QOL showed significant improvement over 1 year without deterioration at 3 months. Our results, showing no negative impact on the functional scales after RP, are consistent with those of a prior German study using EORTC QLQ-C30 and QLQ-PR25 [19] and a U.S. study using SF-36 and UCLA questionnaire [20]. For example, a longitudinal study by Litwin et al [20] reported that over 90% of RP patients reached baseline HRQOL status at postoperative 1 year.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, physical, emotional, and cognitive functioning and global QOL showed significant improvement over 1 year without deterioration at 3 months. Our results, showing no negative impact on the functional scales after RP, are consistent with those of a prior German study using EORTC QLQ-C30 and QLQ-PR25 [19] and a U.S. study using SF-36 and UCLA questionnaire [20]. For example, a longitudinal study by Litwin et al [20] reported that over 90% of RP patients reached baseline HRQOL status at postoperative 1 year.…”
Section: Discussionsupporting
confidence: 91%
“…Emotional functioning showed low ratings at baseline and a significant increase over the five years. This is consistent with Bach et al [ 21 ] who reported similar figures at baseline and an increase after surgery. Wallace et al reported emotions from getting the diagnosis message in a qualitative study of prostate cancer survivors as ‘shock’, ‘body blow’, ‘fear’ and ‘anger’, emotions that may well be reactions in connection with the presentation of a cancer diagnosis [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Jakobsson, Lovén, Hallberg (2004) and Michelsson et al (2000). In a study by Bach et al [ 21 ], ratings for QOL decreased post-operatively, which they did not do in our study. Our study represented a somewhat younger group of men with a wider age range (36-75 years).…”
Section: Discussioncontrasting
confidence: 83%
“…They evaluated the preoperative QoL of 185 patients and compared it with the QoL of an age-matched patient group at least 6 months after prostatectomy. The subgroup analysis of patients older than 70 years showed only a mild reduction of QoL compared with patients younger than 70 years [17].…”
Section: Discussionmentioning
confidence: 95%